Peran Penting Sikap Disiplin Pada Anak - Winda Manik; Meliana Yulan Sari Sagala; Dea Anestia Tampubolon; Damayanti Nababan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
A child's discipline plays a crucial role in shaping their character, academic success, social skills, and mental and emotional well-being. The formation of a strong character begins with the introduction of moral values and the development of independence, which is reinforced by consistent discipline. With a strong discipline, children can manage their time efficiently, develop good study habits, and achieve their maximum academic potential.Furthermore, discipline also positively impacts a child's social skills by helping them build healthy relationships, improve communication skills, and effectively manage conflicts. These abilities are essential in shaping individuals who can collaborate in groups and maintain positive relationships with others. Moreover, discipline also significantly affects a child's mental and emotional well-being. Children with discipline are more capable of managing stress, maintaining emotional balance, and building strong self-confidence. This equips them to face life's pressures with greater calmness and optimism.Thus, a child's discipline is not only a determinant factor in their life success but also a strong foundation for shaping individuals who are morally, intellectually, and emotionally sound. Therefore, it is important for parents, educators, and society as a whole to pay adequate attention to the formation of children's discipline from an early age, as an investment in their bright future.